CLASSROOM MANAGEMENT: EFFECTIVE STRATEGIES FOR CREATING POSITIVE, ENGAGING, AND PRODUCTIVE CLASSROOM ENVIRONMENTS - James Davis (Bright Mind Publishing, 2025)
Classroom management is a critical component of effective teaching and learning. It involves creating an environment where students can engage, learn, and succeed while maintaining positive behaviors and interactions. This paper explores contemporary strategies for classroom management, focusing on those that foster an inclusive, engaging, and productive learning environment. With a particular emphasis on recent advancements in pedagogy, technology, and inclusive practices, this paper discusses how teachers can implement strategies that address diverse student needs and learning styles. The study also explores the role of teacher-student relationships, proactive behavior management, and the integration of technology in promoting positive classroom dynamics. Findings indicate that effective classroom management contributes significantly to student engagement and academic success, as well as to overall school climate.
Keywords: Classroom Management, Positive Environment, Engaging Classroom, Behavior Management, Proactive Strategies, Student Engagement, Technology in Education.